Study Komparasi Hasil Belajar Biologi dengan Penerapan Model Pembelajaran Inquiry Based Learning (IBL) dan Problem Based Learning (PBL) pada Siswa Kelas X SMA Negeri 5 Surakarta Tahun Pelajaran 2013/2014 - Tyas Nyonita; Slamet Santosa; Joko Ariyanto (BIO-PEDAGOGI, 2014)
This study aimed to find out the difference of Biology learning outcome in the applications of Inquiry Based Learning (IBL) and Problem Based Learning (PBL) models in the X graders of SMA Negeri 5 Surakarta in the school year of 2013/2014. This study was a quasi experimental research with posttest only with nonequivalent control group design. This study employed Inquiry Based Learning model in the experiment-1 group and Problem Based Learning in the experiment-2 group. The population of research was all of the X MIPA graders of SMA Negeri Surakarta in the school year of 2013/2014. The sampling technique used was cluster sampling one, so that the X MIPA 2 grade was obtained as experiment 1 and X MIPA 5 grade as experiment 2 groups. Techniques of collecting data used were multiple choice test, observation sheet, and school document. The hypothesis testing was conducted using t-test. From the result of research, it could be concluded that there was a difference of biology learning outcome in the applications of Inquiry Based Learning (IBL) and Problem Based Learning (PBL) models in the X graders of SMA Negeri 5 Surakarta in the school year of 2013/2014. Key Words: Inquiry Based Learning model, Problem Based Learning model, biology learning outcome